The impact of dependencies between climate risks on the asset and liability side of non-life insurers - Nadine Gatzert; Onur Özdil (European Actuarial Journal, 2023)
The aim of this paper is to examine the impact of dependencies between climate transition and physical risks on the default probability and profitability of a non-life insurer focusing on the scenario of a delayed and sudden transition. Toward this end, we suggest a simplified modeling approach for scenario analyses for climate risks affecting assets and liabilities, taking into account potential nonlinear dependence structures. Our results show that dependencies on the liability side and between assets and liabilities in the context of physical-transition scenarios can have a significant impact, particularly on the default risk of a non-life insurer. We additionally analyze the mitigating effects of stop loss reinsurance and risk-adjusted pricing, which—if implementable—seem to be an effective risk management measure against physical climate risks in particular.
Keywords: C51; G22; G32; Q54; 510; Non-life insurance; Collective risk model; Climate risks; Nonlinear dependencies; Asset-liability management